Diagnostic Challenges in Tuberculous Spondylitis in a Young Adult without Overt Immunodeficiency: A Case Report - Ni Putu Nita Wiryandari; I Ketut Agus Somia (MEDICINUS, 2026)
Background: Tuberculous spondylitis accounts for approximately half of all cases of osteoarticular tuberculosis and remains a diagnostic challenge due to its nonspecific clinical manifestations and the variable diagnostic yield of conventionalinvestigations, often leading to delayed diagnosis. Case Presentation: We report a 38-year-old male who presented with chronic nonradiating low back pain for one year, with worsening over one month, followed by paresthesia, urinary incontinence, and progressive bilateral lower limb weakness. The patient had significant weight loss, a close household contact with pulmonary tuberculosis, and lifestyle-related risk factors including smoking and alcohol consumption, but without overt immunodeficiency. Sputum GeneXpert MTB/RIF testing was negative, and histopathological examination of vertebral tissue showed no granulomas or caseous necrosis. However, polymerase chain reaction (PCR) testing of vertebral tissue confirmed the presence of Mycobacterium tuberculosis. Imaging revealed vertebral destruction at T12–L1 withgibbus deformity and a paravertebral soft tissue mass with subligamentous spread on magnetic resonance imaging (MRI). The patient received standard antituberculosis therapy and underwent posterior spinal decompression and stabilizationdue to progressive neurological deficits, resulting in clinical improvement. Conclusion: This case highlights the importance of maintaining a high index of suspicion for tuberculous spondylitis in young adults without classical immunodeficiency and underscores the value of molecular diagnostics when conventional tests are inconclusive.